Thyrotoxic Periodic Paralysis: A Report of 3 Malaysian Cases and a Review of its Pathology - Sthaneshwar, P.; Ramesh, P.; Yap, S.F. (Malaysian Society of Pathologists, 2005)
Thyrotoxic periodic paralysis (TPP) is a medical emergency characterised by sudden onset of muscle weakness with hypokalemia that resolves with the treatment of hyperthyroidism. We report three cases of thyrotoxic periodic paralysis seen at the Accident and Emergency Care Department, University of Malaya Medical Centre in a period of four months. We also review the clinical presentation, pathophysiology, biochemical features and management of TPP. All three patients were young Asian males, presenting with muscle weakness of sudden onset. The first patient presented with lower limb weakness and had symptoms of thyrotoxicosis and goitre. He had a previous similar episode which resolved spontaneously. The second patient presented with quadriplegia, respiratory acidosis and had no signs and symptoms of thyrotoxicosis. The electrocardiogram of this patient showed normal sinus rhythm with U wave in V3 and a flat T wave, which are characteristic of hypokalaemia. The third patient, who was a known case of thyrotoxicosis, was admitted thrice for hypokalemic paralysis during the study period. All cases had low serum potassium, suppressed TSH and elevated T4 confirming thyrotoxic periodic paralysis. Potassium therapy was useful during the crisis; however prophylactic potassium has not been shown to prevent attacks as seen in one of our cases. Conclusion: Thyrotoxic periodic paralysis should be considered in the differential diagnosis of sudden onset paralysis in young male patients. Determination of the plasma potassium levels and thyroid hormones help in the diagnosis. The definitive treatment for TPP is the achievement of euthyroid state.